Handmade greetings for all occasions : 85 cards, gift tags, and invitations]. - Banker, Susan/ Better Homes and Gardens/ Dahlstrom, Carol Field; Better Homes and Gardens Books (Firm) (Des Moines, Iowa : etter Homes and Gardens Books, 2003)
Presents step-by-step instructions for creating eighty- five greeting cards, gift tags, and invitations.
Includes index.
Keywords: Greeting cards; Invitation cards